Lack of awareness and knowledge among people with scabies in a questionnaire based cross sectional and observational study - Rawat, Ritu; Thakur, Dilbag Singh (International Journal Of Community Medicine And Public Health, 2020)
Background: Scabies awareness can decrease the disease health burden. The objective was to assess the awareness and knowledge among people with scabies in a questionnaire based cross sectional, observational study. Methods: Study was questionnaire based, cross sectional, descriptive study. 200 consecutive patients with scabies were enrolled for it. Results: Of the 200 participants, 125 (62.5%) were males and 75 (37.5%) were females. People of all educational levels were affected from scabies ranging from illiterate 25 (12.5%) to graduates 44 (22%). 95 (47.5%) participants did not knew that itching can be because of scabies. 171 (85.5%) participants had no idea of mode of spread of the disease. 199 (99.5%) participants had no knowledge of treatment. None of the participants knew that scabies is preventable. Conclusions: There is a general lack of awareness and knowledge among the people regarding various aspects of scabies. Increased health awareness programmes with more educational and psychosocial support should be provided to the people. Mass drug treatment of scabies in the area should be provided instead of treating the individual patients.